2015
DOI: 10.3109/02699052.2014.976272
|View full text |Cite
|
Sign up to set email alerts
|

Impact of parental acquired brain injury on children: Review of the literature and conceptual model

Abstract: This review summarizes these outcomes, raises conceptual as well as methodological questions to be addressed in future research and eventually presents relevant issues for support and clinical services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…While the impact of ABI on individuals and families, and their corresponding sense of losses, has been well documented, generating knowledge and understanding of families' experiences of living with ABI has largely derived from examination of the subsystems within families-to either present their views of the family or provide their own perceptions of being in the family. Subsystems studied have included the individual with the ABI [1][2][3][4][5][6][7][8]; the caregiver or primary family carer [9][10][11][12][13][14][15][16][17][18], children [19][20][21][22][23], siblings [24][25][26][27][28], and the marital relationship [29][30][31][32][33][34][35][36]. Whilst the subsystem research has provided further understanding of individuals' experiences living with ABI, a family systems approach that studies the family in interaction with each other is limited.…”
Section: Introductionmentioning
confidence: 99%
“…While the impact of ABI on individuals and families, and their corresponding sense of losses, has been well documented, generating knowledge and understanding of families' experiences of living with ABI has largely derived from examination of the subsystems within families-to either present their views of the family or provide their own perceptions of being in the family. Subsystems studied have included the individual with the ABI [1][2][3][4][5][6][7][8]; the caregiver or primary family carer [9][10][11][12][13][14][15][16][17][18], children [19][20][21][22][23], siblings [24][25][26][27][28], and the marital relationship [29][30][31][32][33][34][35][36]. Whilst the subsystem research has provided further understanding of individuals' experiences living with ABI, a family systems approach that studies the family in interaction with each other is limited.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 Beyond effects on behavioral and mental health, parental injury has been found to increase the use of psychoactive medication use by children. 1,[19][20][21] Children of parents treated for unintentional injury were more likely to report posttraumatic stress and depressive symptoms postinjury. 1 Parental TBI has been associated with emotional and behavioral difficulties in children, including depressive symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…1 Parental TBI has been associated with emotional and behavioral difficulties in children, including depressive symptoms. 19,20 Sleep disturbances are prevalent in the pediatric population but may be underdiagnosed. 22 Rates of specific sleep disorders range from 0.004% to 1.2% for parasomnias, 0.005% to 0.2% for circadian-rhythm sleep disorder, 1% for SDB, and 4% to 11% for insomnia.…”
Section: Introductionmentioning
confidence: 99%
“…Some evidence has indicated that parental brain injury is associated with adverse psychological outcomes in children (5,7,8,12,13). Adolescents have reported symptoms of anxiety and depression following parental TBI (8).…”
Section: Introductionmentioning
confidence: 99%